STRESS IMPACT REDUCTION AND PREVENTION OF DEFICITS ASSOCIATED TO RATS AGEING: THE POST-NATAL STIMULATION AND THE ENVIRONMENTAL ENRICHMENT - Ferré, Pilar; Escorihuela, Rosa Mª.; Fernández-Teruel, Albert; Francesc Núñez, Joan; García, Ernesto; González, Berta; Castellano, Bernardo; Tobeña, Adolf (Anales de Psicología / Annals of Psychology)
When organisms perceive any perturbation in the outside word that can disrupt homeostasis, they engage in a set of physiological responses in order to reestablish homeostasis. But, if mantained for a long time, those responses can be damaging and, in fact, they could be related to the appearance of some age-related deficits. Two early manipulations, such as environmental enrichment and postnatal handling have been hypothesized to prevent age-related cognitive and neural deficits in rodents. A long-lasting reduction of emotional reactivity to stress has been proposed as the main mechanism mediating long-term effects of both treatments. The aim of the present work was to revise some previous findings which are in agreement with that proposal, as well as to report some results from our laboratory which replicate and extend that hypothesis.